Adequate calories reduce sarcoperia (AdCaloRes) / Gaithridevi V.Singam - Gaithridevi, V.Singam (2017)
Objective: To evaluate the effect of using daily indirect calorimetry (IC) in determination of the resting energy expenditure (REE) of the patient and achieving the required calories versus standard protocol. To determine the energy balance achieved using IC versus standard protocol. To evaluate the correlation between enegy balance and the quadriceps muscle layer thickness (QMLT) between both group. To determine the protein balance vs the QMLT. To evaluate the correlation between the protein balance and QMLT. Methods: A total of 30 mechanically ventilated patients who were within 48 hours of ICU stay with an expected stay of more than 10 days and had no contraindication to enteral nutrition were included in this study. This was a prospective randomized study with one group receiving standard enteral nutrition protocol and one group receiving enteral nutrition as per guided by IC REE. Both these groups of patients had a 10 day study protocol which included the measurement of REE using IC and the QMLT measurement on day one, day five and day ten. Results: There appeared to be no significant difference between both the control and the interventional arm in terms of caloric and protein prescription and delivery, caloric and protein balance and a correlation between caloric and protein balance with measurement of QMLT. Conclusion: Feeding using standard protocol appears to be as effective in caloric delivery compared to IC but a larger sample size might be necessary to be able to achieve a significant result. Key words: Indirect Calorimetry (IC), Resting Energy Expenditure (REE), Quadriceps Muscle Layer Thickness (QMLT).